Status Gizi dan Kualitas Hidup Lansia yang Tinggal Bersama Keluarga dan pelayanan Sosial Tresna werdha (Nutritional Status and Quality of Life of Elderly People Who’s Lived With Family and Tresna Werdha Social Service in Bondowoso) - Putri Istik Lailiyah; Ninna Rohmawati; Sulistiyani Sulistiyani (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Abstract The number of population and life expectancy of elderly in Indonesia have increased every year. Health problems of elderly are associated with the environmental change and nutritional status that will affect for their quality of life. This research used a cross sectional approach and conducted in Bondowoso area with data at Tresna Werdha Social Service Bondowoso and elderly living in region of Maesan Public Health Centre. This research based on 72 respondents, consist of 36 respondents that living with family and 36 respondents that living in PSTW. The sampling technique used Proportional Random Sampling. Methods of data used questionnaires adapted from WHOQOL-BREF. Data analyzed by Chi Square test (α = 0,05). The results showed that nutritional status of elderly living in PSTW were better than elderly living with their family (p<0,05). Quality of life according of physical health domain, psychological domain, social relationships domain, and over all quality of life of elderly living with their family were better than the elderly living in PSTW (p <0.05). While on quality of life according to environment domain in elderly living with their family and PSTW have same result (p> 0,05). Keywords: elderly,nutritional status, quality of life